KEBIJAKAN FORMULASI SANKSI PIDANA KEBIRI KIMIA DI INDONESIA YANG AKAN DATANG - Endik Wahyudi; Gerry Gerry Joe (MIMBAR YUSTITIA, 2020)
Since the publication of The Substitute Government Regulation (PERPU) No. 1 of 2016 on the second Amendment to Law No. 23 of 2002 on Child Protection, two cases have been decided given chemical castration measures. However, until now the process of funding / sanctions has not been implemented even though it has the power of law anyway. Due to the absence of institutions willing to do so, including Ikatan Dokter Indonesia who felt the sanction was an act that violated the Health Law, as well as the act of chemical castration is seen as retaliation for its actions that of course deviate from the original purpose of funding. This is the background to conducting normative research on the policy of chemicalbirth sanction formulations that apply in Indonesia in the future. This research uses normative research methods, to find the right formulation of sanctions for perpetrators of sexual crimes. The discussion of criminal formulation policy regarding chemical castration as punishment becomes very necessary, seeing its leading sector refuse to be an executor. The act of chemical castration into treatment or treatment of the perpetrator is a solution that can be provided, in line with the statement from ikatan dokter Indonesia, pedophilia is a sexual disorder that occurs due to psychological disorders.